2019
DOI: 10.17576/jsm-2019-4803-05
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Biochemical Changes in Spinach (Spinacea oleracea L.) Subjected to Varying Water Regimes

Abstract: It is known that leafy vegetables including spinach (Spinacea oleracea L.) contain relatively high amount of water, therefore, their water requirement during the life cycle is comparatively more than the other vegetables. In addition, there is an association between osmoprotection and antioxidants with reference to drought stress tolerance. Keeping in mind these facts, the present study was conducted to assess the changes in plant growth, osmoprotectants, chlorophyll pigments and activities/levels of antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 35 publications
6
22
0
Order By: Relevance
“…Besides, the fact that the study was carried out in the winter period and the air was turned off affected the light intensity and changes occurred between the periods. In a water constraint study in spinach, it has been reported that chlorophyll a and b content decreases as drought severity increases (Jabeen et al, 2019). In previous studies, similar results were observed by Akram et al (2016) there were significant differences between the pots in the first three harvests, there was no significant difference between the pots in the final harvest ( Figure 3e).…”
Section: Effect Of Deficit Irrigation On Biochemical Parameterssupporting
confidence: 82%
See 2 more Smart Citations
“…Besides, the fact that the study was carried out in the winter period and the air was turned off affected the light intensity and changes occurred between the periods. In a water constraint study in spinach, it has been reported that chlorophyll a and b content decreases as drought severity increases (Jabeen et al, 2019). In previous studies, similar results were observed by Akram et al (2016) there were significant differences between the pots in the first three harvests, there was no significant difference between the pots in the final harvest ( Figure 3e).…”
Section: Effect Of Deficit Irrigation On Biochemical Parameterssupporting
confidence: 82%
“…As a result of the increased water deficit in spinach, H2O2 increases occurred and became an important criterion for measuring the effect of stress. It has been reported that the content of H2O2 increases with increasing drought stress in spinach (Jabeen et al, 2019). MDA content was found high in all harvests and severe and moderate water constraints.…”
Section: Effect Of Deficit Irrigation On Biochemical Parametersmentioning
confidence: 71%
See 1 more Smart Citation
“…Spinacia oleracea is a worldwide cultivated vegetable crop because of its relative high growth rates, its increased production of biomass and its use of heavy metals and other important soil nutrients [31,32]. Furthermore, S. oleracea has been extensively investigated on the basis of these distinctive features to analyze its growth performance and stress responses to various heavy metals [11,33]. Wastewater irrigation, however, is a common practice in different regions of the world where water shortages are extremely prominent and irrigation puts tremendous pressure on crop quality and yield [6,11,34].…”
Section: Introductionmentioning
confidence: 99%
“…Optimum water availability is one of the major ecological factors that affect the growth and development of plants (Ashraf et al 2010, Jabeen et al 2019). In contrast, if plants are subjected to water deficit conditions, they show stunted growth (Ahammed et al 2020a, 2020b).…”
Section: Introductionmentioning
confidence: 99%